Segregation at source hospital clothing worn by the patient: a systematic review - Rojas Valenciano, Ligia (2016)
Introduction. Segregation and processing of clothing is a vital issue for both patients and human resources working in hospitals and health centers and handling this material. The objective was to evaluate the effectiveness of nursing staff regarding the segregation of hospital origin clothing worn by the patient, for the prevention of nosocomial infections. Method. This is a systematic review, using the recommended by the Cochrane Collaboration methodology. For the identification of studies Electronic searches, online conferences, weekly alerts in BioMed Central journals (e-mail), EBSCO, Clinical Key, PubMed, Journal of infection, Advance of Nursing, Excelencia.net, MEDLINE Journal of Hospital, Cochrane Library Plus. After establishing the criteria for inclusion and exclusion and critical analysis, five documents that would respond to the clinical question they were selected. Result. Segregation of clothing should be made at source (A-III) and recommend handling dirty laundry should be determined locally, in consultation with the local infection control committee. Conclusion. Could not determine the effectiveness of segregation clothing originally performed by nurses in relation to the prevention of nosocomial infections.